Cognitive Impairments in Patients with HIV - Associated Encephalopathy - M, Zokirov. M.; O, Mukhammadjonov (Central Asian Journal of Medical and Natural Science, 2022)
HIV infection is one of the most pressing medical and social problems worldwide today. This article discusses one of the types of complication of HIV-infection as HIV-associated encephalopathy. The clinical features and diagnostic criteria of the disease are considered. Patients were examined using the Montreal Cognitive Assessment Scale and symptomatic treatment with the nootropic drug choline alfoscerate was carried out.